Host Immune Response to Malaria - Trasia, Reqgi First (UNUSA Press, 2021)
Malaria is still a health threat, especially for children and pregnant women in endemic areas. The World Health Organization (WHO) reports 228 million cases of malaria occur worldwide and an estimated 405,000 deaths from malaria globally in 2018. A series of malaria control efforts according to WHO recommendations have been carried out widely. However, these programs face obstacles. Therefore, the existence of an effective malaria vaccine is absolutely necessary in a series of malaria control strategies. Development of a malaria vaccine requires a basic concept regarding the host's immune response to malaria. Unfortunately, only a few in Indonesia have reviewed how the immune response is. This article will present an understanding of how the human immune system responds to Plasmodium falciparum.